2015
DOI: 10.1038/mp.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum VEGF levels with prefrontal cortex volume in schizophrenia

Abstract: A large body of evidence indicates alterations in brain regional cellular energy metabolism and blood flow in schizophrenia. Among the different molecules regulating blood flow, vascular endothelial growth factor (VEGF) is generally accepted as the major factor involved in the process of angiogenesis. In the present study, we examined whether peripheral VEGF levels correlate with changes in the prefrontal cortex (PFC) volume in patients with schizophrenia and in healthy controls. Whole-blood samples were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 77 publications
2
47
2
1
Order By: Relevance
“…In vitro data have shown that pro-inflammatory cytokines (TNF-α, IL-1β, and IFN-γ) cause a dose-dependent increase in BBB permeability by (a) inducing expression of adhesion molecules such as ICAM-1 and VCAM-1 on the luminal surface of BBB endothelial cells in animals (91–93) and humans (94), which facilitates transendothelial lymphocyte and monocyte migration; (b) causing vascular endothelial oxidative injury by impairing vascular endothelial mitochondrial oxidative metabolism (65, 95); and (c) directly damaging endothelial tight junctions (11, 16). More recently, an association was described between elevated serum IL-6 and VEGF levels in schizophrenia (40), supporting the role of inflammation in inducing BBB hyperpermeability in schizophrenia. More studies are needed to fully explore the relevance of these mechanisms to the onset and progression of schizophrenia pathology.…”
Section: Theoretical Integration Of Oxidative and Neuroinflammatory Mmentioning
confidence: 81%
See 2 more Smart Citations
“…In vitro data have shown that pro-inflammatory cytokines (TNF-α, IL-1β, and IFN-γ) cause a dose-dependent increase in BBB permeability by (a) inducing expression of adhesion molecules such as ICAM-1 and VCAM-1 on the luminal surface of BBB endothelial cells in animals (91–93) and humans (94), which facilitates transendothelial lymphocyte and monocyte migration; (b) causing vascular endothelial oxidative injury by impairing vascular endothelial mitochondrial oxidative metabolism (65, 95); and (c) directly damaging endothelial tight junctions (11, 16). More recently, an association was described between elevated serum IL-6 and VEGF levels in schizophrenia (40), supporting the role of inflammation in inducing BBB hyperpermeability in schizophrenia. More studies are needed to fully explore the relevance of these mechanisms to the onset and progression of schizophrenia pathology.…”
Section: Theoretical Integration Of Oxidative and Neuroinflammatory Mmentioning
confidence: 81%
“…Therefore, genetically predetermined heparan sulfate abnormalities may increase BBB hyperpermeability and facilitate transendothelial leukocyte migration in some individuals with schizophrenia (34). Recent studies have documented elevated serum levels of vascular endothelial growth factor (VEGF) (40) and significantly reduced expression of VEGF receptor 2 in the prefrontal cortex (41), which likely reflects its accelerated destruction by increased levels and activity of VEGF in individuals with schizophrenia. VEGF regulates angiogenesis and increases BBB permeability (40).…”
Section: Bbb Hyperpermeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is associated with inflammation reaction. Its serum levels are related to prefrontal cortex abnormalities in schizophrenia [71]. Shortened telomere length is found in unremitted schizophrenic patients [72].…”
Section: Resultsmentioning
confidence: 99%
“…In SZ, post mortem brain analysis demonstrated that dysregulated VEGF signaling occurs in both the dorsolateral prefrontal cortex (Fulzele and Pillai, 2009) and thalamus (Chu et al , 2009). Recently, Pillai et al demonstrated that serum VEGF levels were associated with prefrontal cortical volume (Pillai et al , 2015). These studies demonstrate that an imbalance of angiogenesis regulation can have detrimental effects.…”
Section: Discussionmentioning
confidence: 99%